Связь личностной открытости с адаптационными резервами человека - Касап, О.В.; Луценко, Е.Л. (My University, 2014)
This article is devoted to the researching of connections between adaptation reserves of a person and one’s openness, which is considered in its external and internal aspects. The submitted research has proved an existence of required connections.
Keywords: личностная открытость; психофизиология; защитные механизмы; макиавеллизм; достоверность ответов; вариабельность сердечного ритма; адаптация